2018
DOI: 10.1038/s41598-018-19311-3
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis serine/threonine/tyrosine protein kinase phosphorylates oil body proteins that regulate oil content in the seeds

Abstract: Protein phosphorylation is an important post-translational modification that can regulate the protein function. The current knowledge on the phosphorylation status of plant oil body (OB) proteins is inadequate. This present study identifies the distinct physiological substrates of Arabidopsis serine/threonine/tyrosine protein kinase (STYK) and its role in seed oil accumulation; the role of Arabidopsis OLE1, a major seed OB protein has also been elucidated. In vitro kinase assay followed by mass spectrometry id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 36 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…The replacement of Pro residue can lead to abnormal targeting of the OB [ 19 ]. The N- and C-terminal amphiphilic domains, located on the surface of the oil body, can not only maintain the size of the OB through their steric hindrance and electronegative repulsion [ 20 ] but also regulate the OB by combining it with metabolic enzymes and regulatory proteins [ 21 23 ]. Take together, oleosins are involved in the oil bodies regulation and biosynthesis, and metabolism of lipid [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The replacement of Pro residue can lead to abnormal targeting of the OB [ 19 ]. The N- and C-terminal amphiphilic domains, located on the surface of the oil body, can not only maintain the size of the OB through their steric hindrance and electronegative repulsion [ 20 ] but also regulate the OB by combining it with metabolic enzymes and regulatory proteins [ 21 23 ]. Take together, oleosins are involved in the oil bodies regulation and biosynthesis, and metabolism of lipid [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Members of the STY kinase family are dual-specificity kinases that possess catalytic Ser/Thr and Tyr domains, and they regulate some plant metabolic and developmental processes through phosphorylation of target proteins [24,25]. For example, STY protein kinases appear to have important roles in ammonium transport in rice seedling roots [26], in storage oil accumulation in Arabidopsis siliques [27], and in stress response and seed development in cucumber and peanuts [28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Some genes involved in protein post-translational modification, such as protein phosphorylation (Protein kinase superfamily protein) and ubiquitination ( UBC5 ), were also tightly co-expressed with fatty acid biosynthesis genes. Previous studies have shown that a serine/threonine/tyrosine protein kinase participated in the regulation of the content and composition of the Arabidopsis seed oil by mediating phosphorylation of oil body proteins ( Ramachandiran et al, 2018 ). It has also been revealed that the seed-expressed casein kinase I enhanced the bHLH -mediated transactivation of the FAD2 gene promoter via phosphorylation of the bHLH transcription factor ( Kim et al, 2010 ), while the ubiquitin proteasome pathway modulated FAD3 protein amounts in response to temperature ( O’Quin et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%